Woman movements: Preservation of ethnocultural traditions - Elena Venidiktova, Adelya Sattarova, Diana Sabirova, Irina Kondrateva, (Opción, 2019)
The purpose of the article is the identification of a role of women Tatar groups of Republic of Tatarstan in public and cultural development through XX-XXI centuries via structural, historical, anthropological and functional approaches. As a result, authors seek for lighting those issues connected with the Muslim world. If there is no woman in a family, then there is no family. In conclusion, in a way of life of modern Tatar women, among youth, the activity in public and cultural and confessional life, in the revival of spiritual ethnocultural traditions of the Tatar people is shown.